Evaluation of Technological Pedagogical Content Knowledge (TPACK) Teachers of SMK Negeri 6 Malang (Case Study of Electrical Power Installation Engineering and Autotronic Engineering) - Ferdiansyah, Dodik Septian; Patmanthara, Syaad; Suswanto, Hary (Technium Social Sciences Journal, 2022)
This study aims to determine the level of Technological Pedagogical Content Knowledge (TPACK) proficiency. This type of research is descriptive quantitative research. The instruments used to measure TPACK are in the form of questionnaires and interview questionnaires using a Likert scale with 5 scales. The samples of this study were Electrical Power Installation Engineering (EPIE) teachers at SMK N 6 Malang, totaling 7 people and Autotronic Engineering (AE) teachers at SMK N 6 Malang totaling 6 people. The results of the study are EPIE teachers' TK skills are in very good criteria with an average of 68, while AE teachers' kindergarten skills are in good criteria with an average of 53. EPIE teachers' PK skills are in good criteria with average - an average of 67.3, while the PK skills of AE teachers are in good criteria with an average of 75.2. EPIE teachers' CK skills are in very good criteria with an average of 31, while the CK skills of AE teachers are in very good criteria good with an average of 31. EPIE teachers' TCK skills are in very good criteria with an average of 26, while AE teachers' TCK skills are in good criteria with an average of 22. EPIE teachers' PCK skills are at criteria very good with an average of 57, while the PCK skills of AE teachers are in very good criteria with an average of 56. EPIE teachers' TPK skills are in good criteria with an average of 26.6, while the TPK skills of AE teachers are at good criteria with an average of 26.8. EPIE teachers' TPACK skills are in good criteria with an average of 18.4, while AE teachers' TPACK skills are in good criteria with an average of 18.2.